BOGOR REGENCY: EVALUATING ECONOMIC SECTOR POTENTIAL USING THE LQ METHOD AND KLASEN TYPOLOGY - Hamzah, Hamzah; Armadi, Dion Achmad; Kusumawati, Riny; Shandra, Meira Putri (Universitas Pakuan, 2024)
ABSTRACTThe aim of this research is to analyze the economic sectors of a region that utilize the base sector or leading sector and to obtain an overview of the pattern and structure of regional economic growth. The data used is secondary data obtained from BPS Bogor Regency, and the analysis techniques used are Location Quotient and Klassen Typology. The research results show that the 40 sub-districts have different potential for each economic base. Six sectors are included in the underdeveloped sector quadrant (requiring special attention): eight developing sectors, two potential sectors, and one prime sector. Nanggung sub-district is a sub-district that is growing rapidly with the mining sector. At the same time, Ciseeng and Sukamakmur sub-districts have not experienced significant changes from year to year and should be of concern to the Bogor Regency government. Things that the Bogor Regency government can do include improving basic infrastructure, improving education and health facilities, and providing capital and training for village communities.ABSTRAKTujuan dari penelitian ini adalah menganalisis sektor – sektor ekonomi suatu wilayah yang memanfaatkan sektor basis atau leading sector dan untuk mengetahui gambaran tentang pola dan struktur pertumbuhan ekonomi daerah. Data yang digunakan adalah data sekunder yang diperoleh dari BPS Kabupaten Bogor dengan teknik analisis yang digunakan adalah Location Quotient dan Tipologi Klassen. Hasil penelitian menunjukkan bahwa dari 40 kecamatan memiliki potensi yang berbeda untuk setiap basis ekonomi. Terdapat enam sektor yang termasuk dalam kuadran sektor terbelakang (perlu perhatian khusus), delapan sektor berkembang, dua sektor potensial dan satu sektor prima. Kecamatan Nanggung menjadi kecamatan yang berkembang pesat dengan adanya sektor pertambangan, sedangkan Kecamatan Ciseeng dan Sukamakmur menjadi kecamatan yang tidak mengalami perubahan signifikan dari tahun ke tahun dan harus menjadi perhatian pemerintah Kabupaten Bogor. Hal yang dapat dilakukan oleh pemerintah Kabupaten Bogor antara lain perbaikan infrastruktur dasar, peningkatan fasilitas pendidikan dan kesehatan, pemberian modal dan pelatihan bagi masyarakat desa.